Broadband wireless communications for railway applications : for onboard internet access and other applications - Masson, Émilie, 1982-; Berbineau, Marion (Springer, 2016)
This book focuses on the needs of railway operators in terms of wireless communications, divided in two main categories: the commercial services and the operational needs. Then, all available technologies that can be used to provide Internet access on board trains and all the other operational applications requiring high capacity are detailed. Finally, challenges and trends in railway telecommunications are highlighted, through the presentation of the future and emerging technologies, the current discussions and works in the different authorities, and the key challenges and scientific barriers.
Keywords: Railroads -- Communication systems.; Broadband communication systems.; elektronické knihy; electronic books